State-religion Relations in Azerbaijan During Tsarist Russia - Mammadov, Jeyhun (Scholarya Demo Journal of Ruby, 2019)
The article talks about the relations between the state and religion in Azerbaijan and the state policy implemented in this sphere during Tsarist Russia. It is noted that this stage was one of the most difficult and painful periods in the history of Azerbaijan. It deals with the transformation of the Tsarist Russia's religious activity after the occupation of Azerbaijan into an integral part of the policy of colonialism, plundering as much as possible of Northern Azerbaijan by the colonial administration, not allowing the creation of a national state, making the principles of strengthening its forposts even with more ethnic-religious jealousy. It also widely states that the creation of an Armenian state on Azerbaijani lands was a long-term plan of the Russian Empire, as well as some European countries, and that step-by-step perfidious efforts have been made to implement this policy. The article notes the works done for the purpose of “Russification” and “Christianization” of Azerbaijanis, the policy of “resettlement”, as well as discrimination against the representatives of different regions, religious people, restriction of their rights and privileges, their persecution, expulsion and execution. The article provides detailed information on the documents adopted during the Tsarist government, the rights of religious figures to receive education, the duties of sheikh-ul-islam and mufti institutions, and reflects the activities of intellectuals who contributed to the culture and science of Azerbaijan at that time. Finally, it notes that despite all efforts of the Tsarist government, the Azerbaijani people didn't deviate from their traditions and religious beliefs and could maintain their spiritual values.